Innovative management of severe tracheobronchomalacia using anterior and posterior tracheobronchopexy. (25th March 2019) - Lawlor, Claire; Smithers, Charles Jason; Hamilton, Thomas; Baird, Christopher; Rahbar, Reza; Choi, Sukgi; Jennings, Russell
Abstract : Objectives/Hypothesis: Combined anterior and posterior tracheobronchopexy is a novel surgical approach for the management of severe tracheobronchomalacia (TBM). We present our institutional experience with this procedure. Our objective was to determine the utility and safety of anterior and posterior tracheopexy in the treatment of severe TBM. Study Design: Retrospective chart review. Methods: All patients who underwent anterior and posterior tracheopexy from January 2013 to July 2017 were retrospectively reviewed. Charts were reviewed for indications, preoperative work‐up, tracheobronchomalacia classification and severity, procedure, associated syndromes, synchronous upper aerodigestive tract lesions, and aberrant thoracic vessels. Main outcomes measured included improvement in respiratory symptoms, successful extubation and/or decannulation, vocal fold immobility, and new tracheotomy placement. Results: Twenty‐five patients underwent anterior and posterior tracheopexy at a mean age of 15.8 months (range, 2–209 months; mean, 31 months if 2 outliers of 206 and 209 months included). Mean length of follow‐up was 26.8 months (range, 13–52 months). Indications for surgery included apneic events, ventilator dependence, need for positive pressure ventilation, tracheotomy dependence secondary to TBM, recurrent pneumonia, and exercise intolerance. Many patients had other underlying syndromes and synchronous upper aerodigestive tract lesions (8 VACTERL, 2 CHARGE, 1 trisomy 21, 1 Feingold syndrome, 17 esophageal atresia/tracheoesophageal fistula, 20 cardiac/great vessel anomalies, 1 subglottic stenosis, 1 laryngomalacia, 7 laryngeal cleft). At preoperative bronchoscopy, 21 of 25 patients had >90% collapse of at least one segment of their trachea, and the remaining four had 70% to 90% collapse. Following anterior and posterior tracheopexy, one patient developed new bilateral vocal‐fold immobility; one patient with a preoperative left cord paralysis had a new right vocal‐fold immobility. Postoperatively, most patients had significant improvement in their respiratory symptoms (21 of 25, 84%) at most recent follow‐up. Three patients with preexisting tracheotomy were decannulated; two patients still had a tracheotomy at last follow‐up. Two patients required new tracheotomy for bilateral vocal‐fold immobility. Conclusions: Combined anterior and posterior tracheopexy is a promising new technique for the surgical management of severe TBM. Further experience and longer follow‐up are needed to validate this contemporary approach and to minimize the risk of recurrent laryngeal nerve injury. Level of Evidence: 4 Laryngoscope, 130:E65–E74, 2020